Key astroglial markers in human liver cirrhosis of different degree: immunohistochemical study - T. V. Shulyatnikova; V. O. Tumanskyi (Zaporožskij Medicinskij Žurnal)
The aim of the study – determining the immunohistochemical levels of the GFAP, GS and AQP4 in different regions of the human brain in the conditions of liver cirrhosis of different degree.